Measuring supplier's service quality and customer satisfaction using servqual / Hirun Azaman Ismail - Ismail, Hirun Azaman (2004)
Service quality can be used as a strategic differentiation weapon to build an organizational distinctive advantage. To be competitive, service supplier should embrace customer-driven quality which represents a proactive approach in satisfying the needs of the customers by gathering information about their needs and preferences and then designing and delivering the service that satisfy them. Service suppliers should continuously monitor the service qualify perception of its customers, and make necessary improvements of the design and the delivery of the service. This study attempts to determine the expectations, perceptions, and the level of satisfaction of the Kangar General Hospital staff on the quality of services given by the Faber Medi-Serve as a contract hospital service provider. The internationally used SERVQUAL model is applied. An analysis of the staff responding to the survey revealed that there was an overall service quality gap between staff's perceptions and expectations across all of the five service quality dimensions namely, in tire order of magnitude, responsiveness, reliability, assurance, empathy and tangibility.